Thermodynamic modelling and performance study of an engine waste heat driven adsorption cooling for automotive air-conditioning - Ali, Syed Muztuza (2016)
Waste heat from engine can be utilized to drive an adsorption cooling system for air conditioning purposes in the vehicle cabin, which not only improves the fuel economy but also reduces the carbon footprint. It is also important to reduce the size of the adsorption bed to adopt the adsorption technology for air-conditioning applications in passenger cars, buses and trucks or even trains. In this article, we present a two stage indirect exhaust heat recovery system of automotive engine employing an effective lumped parameter model to simulate the dynamic behaviors of an adsorption chiller that ranges from the transient to the cyclic steady states. The thermodynamic framework of adsorption chiller is developed from the rigor of mass and energy balances of each component of the system and experimentally confirmed isotherms and kinetics data of various adsorbent–adsorbate pairs. The performance factors are calculated in terms of COP (Coefficient of Performance) and SCP (Specific Cooling Power) for different operating parameters such as cycle time, exhaust gas temperatures, cooling water temperatures and flow rates. From the simulation results, it is found that the exhaust energy of a six cylinder 3000 cc private car is able to produce nearly 3 kW of cooling power for the car cabin. It is also observed that the driving heat source temperature does not remain constant throughout the cycle time unlike the conventional adsorption chiller, and the hot water temperatures as driving source vary from 65 to 95 °C. CaCl2-in-silica gel–water system is found better in terms of COP and SCP as compared with other adsorbents – water systems.